Aerobic Training, But Not Creatine, Modifies Longissimus Dorsi Muscle Composition - D'Angelis, Flora H.F. [UNESP]; Mota, Marcílio D.S. [UNESP]; Freitas, Eduardo V.V. [UNESP]; Ferraz, Guilherme C. [UNESP]; Abrahão, André R. [UNESP]; Lacerda-Neto, José C. [UNESP]; Queiroz-Neto, Antonio [UNESP] (Elsevier, 2007)
The goal of this study was to investigate by means of an ultrasound examination the composition of the longissimus dorsi muscle in 12 purebred Arabian horses submitted to aerobic training for 90 days, with and without creatine supplementation. Creatine supplementation was carried out by daily administration of 75 g creatine monohydrate mixed into the ration during 90 days of training. Physical conditioning was conducted on a high-performance treadmill, and training intensity was stipulated by calculating the velocity at which blood lactate reaches 4 mmol/l, determined monthly for each animal. The individual intensity of physical force was established at 80% of velocity that resulted in a blood lactate level of 4 mmol/l. The cross-sectional area and the thickness of the layer of fat of the longissimus dorsi muscle were measured for each group at the end of 8 months of inactivity and after 30, 60, and 90 days of training without (control groups) or with creatine supplementation (experimental groups). The results showed that aerobic training combined with or without creatine supplementation caused significant longissimus dorsi hypertrophy and reduction in the thickness of the fat layer. No beneficial effect from prolonged creatine supplementation on the body composition of horses was detected. © 2007 Elsevier Inc. All rights reserved.
Keywords: Aerobic training; Creatine; Horse; Longissimus dorsi; Ultrasound; Animalia; Equidae